2005
DOI: 10.1097/01.wnf.0000175523.33334.24
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Agonist Pergolide Prevents Levodopa-Induced Quinoprotein Formation in Parkinsonian Striatum and Shows Quenching Effects on Dopamine-Semiquinone Generated in Vitro

Abstract: The neurotoxicity of dopamine (DA) quinones that appears in dopaminergic neuron-specific oxidative stress has recently been shown to play a role in the pathogenesis and/or progression of Parkinson disease. To clarify the effects of a DA agonist, pergolide, on the levodopa-induced elevation of quinones, the authors examined striatal changes in quinoprotein using a hemi-parkinsonian mouse model. The level of striatal quinoprotein was significantly elevated specifically on the parkinsonian side, but not on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…We reported that pergolide and pramipexole scavenged DA-semiquinone generated in vitro in a dose-dependent manner [33]. Pergolide completely blocked the increase of striatal quinoprotein level, which elevated specifically on the parkinsonian side of hemi-parkinsonian mice with repeated L-DOPA administration [8]. These quenching effects of DA agonists against cytotoxic DA quinones could play a key role in its neuroprotective mechanism in the parkinsonian brain.…”
Section: Da Agonistsmentioning
confidence: 94%
See 2 more Smart Citations
“…We reported that pergolide and pramipexole scavenged DA-semiquinone generated in vitro in a dose-dependent manner [33]. Pergolide completely blocked the increase of striatal quinoprotein level, which elevated specifically on the parkinsonian side of hemi-parkinsonian mice with repeated L-DOPA administration [8]. These quenching effects of DA agonists against cytotoxic DA quinones could play a key role in its neuroprotective mechanism in the parkinsonian brain.…”
Section: Da Agonistsmentioning
confidence: 94%
“…Furthermore, the ELLDOPA study, which tried to clarify whether or not L-DOPA is toxic and accelerates the progression of Parkinson's disease, showed that long-term L-DOPA treatment improved clinical PD symptoms but decreased striatal DA uptake (b-CIT) in SPECT as a functional marker of DAT and caused adverse events of dyskinesia [32]. Indeed, we previously reported that repeated L-DOPA administration (50 mg/kg/day) for 7 days elevated striatal DA turnover (2.7-fold) and quinone generation (2.4-fold) specifically on the parkinsonian side, but not on the control side, of hemi-parkinsonian models [8,33,34]. Therefore, the excess amount of cytosolic DA outside the synaptic vesicles after L-DOPA treatment may exert functional inhibitory effects on DA re-uptake through dysfunction of DAT (decline of b-CIT uptake) by probably quinone generation, but not neurodegenerative effects on dopaminergic neurons.…”
Section: Involvement Of Da Quinone Formation In Dopaminergic Neurotoxmentioning
confidence: 97%
See 1 more Smart Citation
“…We recently revealed that the DA agonists pergolide and pramipexole possess not only ROS/RNS-scavenging activities and glutathione-increasing effects, but also a quenching effect on DA-semiquinone radicals generated in vitro [109,110]. In particular, pergolide dramatically prevents repeated L-DOPA administration-induced striatal quinone generation specifically in the lesioned side of hemiparkinsonian models [109]. Regarding the specificity to the dopaminergic neuronal system and the clinical efficacy, DA agonists may be the most potential therapeutic reagents against DA quinone-induced toxicity.…”
Section: Protective Molecules and Drugs Against Dopamine Quinoneinducedmentioning
confidence: 99%
“…Furthermore, the Earlier versus Later Levodopa (ELLDOPA) study, which tried to clarify whether or not L-DOPA is toxic and accelerates the progression of PD, showed that L-DOPA-treated patients had an increased rate of decline in striatal DA uptake (β-CIT) in single photon emission computed tomography (SPECT), although patients treated with L-DOPA showed less clinical deterioration [107]. We previously revealed that repeated L-DOPA administration (50 mg/kg/day) for 7 days elevated striatal DA turnover (2.7-fold) and quinone generation (2.4-fold) specifically in the parkinsonian side, but not in the control side, of hemiparkinsonian models [108][109][110]. Therefore, the excess amount of cytosolic DA outside of the synaptic vesicles after L-DOPA treatment may exert neurodegenerative effects through quinone generation, at least in the damaged dopaminergic nerve terminals.…”
Section: Quinone Formation As a Dopaminergic Neuron-specific Oxidatimentioning
confidence: 99%